Pengaruh Pembelajaran Pegon Terhadap Keterampilan Menulis Bahasa Arab Di Kelas Satu Madrasah Diniyah Sunan Kalijogo Jabung - Taufikur Rohman B P; Ahmad Nuruddin (Muhadasah: Jurnal Pendidikan Bahasa Arab, 2024)
The learning of pegon writing has many similarities in several methods of learning writing skills, this is because there are many letters in pegon writing with Arabic writing, so in this case the researcher found an increase in Arabic writing, especially in the verses of the Qur'an. In this case, researchers are interested in conducting research related to this matter, with the aim of knowing the effect of pegon learning on Arabic writing skills in grade 1 of Madrasah Diniyah Sunan Kalijogo Jabung. This research uses a quantitative research approach with the type of field research or field research. The research instrument is a questionnaire and the data collection techniques used are documentation and questionnaires. The sample of this study was grade 1 students as many as 30 students. Instrument analysis includes reliability test, normality test, homogeneity test, linearity test, and descriptive test. Data is analyzed using validity test, reliability test, normality test, homogeneity test, linearity test, and descriptive test, simple linear test, coefficient of determination test, and t test and draw conclusions. The results showed that the implementation of pegon learning had a positive effect on Arabic writing skills with the value of t count greater than t table, namely 5.307> 2.049 with a significance level of 0.000 <0.05. Based on the simple linear regression test, the result is 0.501 with a percentage of influence of 50.1% which means sufficient. It can be concluded that pegon learning proved to be quite effective in Arabic writing skills in this study. So that pegon learning that has been implemented in class I of Madrasah Diniyah Sunan Kalijogo Jabung can be well received and can continue to be applied by teachers during the learning process in the next class.